AB1019 Chronic Nonbacterial Osteomyelitis in a Pediatric Population: A Multicenter Observational Study. (9th June 2015) - Pastore, S.; Ferrara, G.; Sandrin, C.; Breda, L.; Alessio, M.; Teruzzi, B.; Martino, S.; Gerloni, V.; Cattalini, M.; Meini, A.; La Torre, F.; Lepore, L.; et al.
Abstract : Background: Chronic nonbacterial osteomyelitis (CNO) is a rare inflammatory disorder that primarily affects children. Its hallmark is recurring episodes of sterile osteomyelitis. The clinical presentation is insidious onset of bone pain with or without fever. Pathogenesis is still unknown. Objectives: We conducted a retrospective review to assess the clinical characteristics and treatment responses of a cohort of pediatric CNO patients. Methods: Children diagnosed with CNO at 8 tertiary care centers in Italy between 2004 and 2014 were identified. Clinical, laboratory, radiological and histological data were obtained. Results: Forty-seven patients with CNO (33 females, 14 males) were identified. The average follow up was 34 months (range 2 – 144 months). Bone pain was the leading symptom; median age of first complaint was 9 years (range 4-14 ys). A total of 210 localizations were found with a median of 4 localizations for patient. The majority of bone lesions were located in the metaphyses of the long bones (38%), vertebral column (35%), pelvis (12%) and clavicle (8%). Six patients had only one localization and 3 of them had the clavicle involvement. Sixteen out of 47 patients (34%) presented extra-articular symptoms: fever (13), psoriasis (5, one of them had acrodermatitis continua of Hallopeau), proteinuria (4), growth failure (2), acne (2), pustolosis (2), acrocyanosis (1). One out of 4 patients with proteinuria underwent renal biopsy that showed a mesangial glomerulonephritis. One other patient presented a steroid-dependent nephrotic syndrome before the onset of bone symptoms; renal biopsy showed a minimal change glomerulonephritis disease. At onset blood examination revealed pronounced increased eritrosedimentation rate (ESR) and C-reactive protein (CRP) in 18 cases (38%); slight increased ESR and CRP in 7 cases (15%). In 35/47 (74%) patients diagnosis was formalized after biopsy. In the remaining patients diagnosis seemed clear for multifocal pattern, the peculiar localizations and/or the typical MRI images. NSAIDs were the first line therapy in all patients, with achievement clinical remission in 12/47 (25%). Corticosteroids were used in 24/47 patients with good response only in 12% of them. Among the other patients we chose bisphosphonate with good percentage of clinical remission (18/26, 70%). Conclusions: In a Italian cohort of 47 children with CNO, skin and renal involvement were detected. Bisphosphonates were more likely to lead to clinical remission than NSAIDs and corticosteroids. So we think that CNO patients need a strict renal function control and bisphosphonates should be the first choice second-line treatment. Disclosure of Interest: None declared